Identification of Streptococcus porcinus from human sources. - Facklam, R (1995)
Streptococcus porcinus is normally associated with infections in swine. Cultures of this streptococcal species are rarely reported from human infections. In the past 10 years, we have identified 13 cultures of S. porcinus from human sources from persons living in the United States and Canada. Seven of the strains were identified in the past 15 months. Nine of the strains were of a single serogroup, provisionally called C1. In addition, nine of the strains were isolated from the genitourinary tract of reproductive-age female patients, some with delivery problems. S. porcinus strains could be identified by hemolytic, serologic, and physiologic characteristics. All strains were susceptible to penicillin, erythromycin, and other antimicrobial agents. Fifty-four percent of the strains were resistant to tetracycline. These findings suggest that we may be seeing a change in the flora of the genitourinary tract of humans. Whether these isolates are significant pathogens is unknown at this time.